Entry Mode Choices of Foreign Financial Institutions and the Potential Effect of Regulatory Reform: An Explorative Study of South Korean Asset Management Industry - Jung, Ki Yeon (2008)
The study over the South Korean asset management industry has not been comprehensively conducted in terms of breadth and depth. More foreign financial institutions (FFIs) are being involved in this market due to its potential growth. In particular, the current regulatory reform implemented by Korean government is expected to bring a major revamp in Korean financial industry including asset management industry. In this aspect, this case study aims to provide the most updated snapshot of Korean asset management industry (AMI), with a particular focus given on the FFI entry mode choice and the potential effect of the most recent regulatory reform on FFI's internationalization strategy. The data collected from various channels indicated that the entries of FFIs in Korean AMI gradually increased from 1997 to 2007. It is interpreted that the local government's regulatory reforms resulted in such an increase of FFI's market entry to Korean AMI. FFI market entry was encouraged in 2004 when local government released further deregulation proposal of FISCMA when IIAMBA was already in force. The data also demonstrate that FFIs preferred to enter Korean AMI using partnering mode more than buying and building during the period. However, from year 2004 to 2007, annual entry of FFIs increased but FFIs did not show any specific preference on entry mode choice. This research also found out that a linkage exists between internationalization of FFIs and financial deregulation in Korean AMI. Such regulatory reform also delivers an important message to FFIs which plan to exploit this bonanza. When FISCMA takes effect in Korean AMI, the entry barrier becomes lower, and the possibility of consolidation with other financial institutions (both AMCs and non-AMCs) increases which in turn will make the market more competitive. Firstly, the entry of FFIs is predicted to increase and the entry mode choices of FFIs more diversified. Secondly, a FFI is likely to face a decision about consolidation with domestic AMCs or other non-AMC financial institutions. Thirdly, the increased competition led by the regulatory reform is expected to bring Wimbledon effect, which is likely to bring a consequence of the market dominance by FFIs. In conclusion, the research finished with providing limitations and recommendations for future studies.